On the interaction between spread foundations and tie-beams under eccentric loading. (1st February 2020) - Pane, Vincenzo; Bellavita, Diego; Castori, Giulio; Vecchietti, Alessia; Cecconi, Manuela
Highlights: Ability of tie-beams to absorb part of the bending moments is investigated. Internal forces are related to the relative rotational stiffness of the whole system. Proposal of a simple approach to evaluate actions on foundation ground and tie-beams. A significant advantage – in terms of foundation size and cost – can be obtained. Abstract: In framed r.c. or steel structures it is common practice to connect spread footings and strip foundations by means of tie-beams. While such beams are often required to absorb axial forces deriving from horizontal relative displacements at the foundation level, their ability to distribute and reduce the bending moments transferred to the ground is typically neglected. The present work shows that a significant advantage – in terms of foundation size and cost – can be obtained by considering the ability of tie-beams to absorb part of the bending moments which are normally attributed to the foundations alone. To this aim, it is first demonstrated that the distribution of internal forces in the soil-foundation-beam system is exclusively governed by a dimensionless parameter representing the relative rotational stiffness of the system. A simple approach is then proposed to evaluate the actions on both foundation ground and tie-beams, using a numerical model or, alternatively, an approximate method based on the superposition of effects. Finally, some examples are given to point out the usefulness of the proposed approach in terms of reduction of load eccentricity at the foundation bearing level, leading to a sensible reduction of foundations cost.